2004
DOI: 10.1186/1471-2474-5-35
|View full text |Cite
|
Sign up to set email alerts
|

A high prevalence of cumulative trauma disorders in Iranian instrumentalists

Abstract: BackgroundCumulative trauma disorders (CTDs) are common in musicians and their prevalence has been the subject of a number of studies in most western countries. Such studies are scarce in developing countries despite the possibility that CTDs may have a different prevalence in these countries, especially when considering traditional musical instruments and different methods of playing. Although not formally studied before, according to our experience the prevalence of CTDs seemed to be high among Iranian instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In previous studies, musicians have reported musculoskeletal symptoms at multiple anatomic sites. Most studies report the fingers, hands, and wrist as the region with the highest symptoms prevalence ranging from 13 to 63% of those sampled [Hochberg et al, 1983;Caldron et al, 1986;Fry, 1986Fry, , 1987Revak, 1989;Larsson et al, 1993;DeSmet et al, 1998;Blackie et al, 1999;Shields and Dockrell, 2000;Pak and Chesky, 2001;Sadeghi et al, 2004]. Other affected areas include the neck, shoulders, arms, and back [Caldron et al, 1986;Fry, 1986Fry, , 1987Hiner et al, 1987;Middlestadt and Fishbein, 1989;Revak, 1989;Larsson et al, 1993;Fjellman-Wiklund and Sundelin, 1998;Blackie et al, 1999;Shields and Dockrell, 2000;Ackerman and Adams, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, musicians have reported musculoskeletal symptoms at multiple anatomic sites. Most studies report the fingers, hands, and wrist as the region with the highest symptoms prevalence ranging from 13 to 63% of those sampled [Hochberg et al, 1983;Caldron et al, 1986;Fry, 1986Fry, , 1987Revak, 1989;Larsson et al, 1993;DeSmet et al, 1998;Blackie et al, 1999;Shields and Dockrell, 2000;Pak and Chesky, 2001;Sadeghi et al, 2004]. Other affected areas include the neck, shoulders, arms, and back [Caldron et al, 1986;Fry, 1986Fry, , 1987Hiner et al, 1987;Middlestadt and Fishbein, 1989;Revak, 1989;Larsson et al, 1993;Fjellman-Wiklund and Sundelin, 1998;Blackie et al, 1999;Shields and Dockrell, 2000;Ackerman and Adams, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalences of up to 80% have been reported among amateur musicians. [ 8 12 ] These numbers seem to outline the prevalence of musculoskeletal complaints in the open population, for example in the Netherlands a year prevalence of 53.4% is reported in a survey in the open population. [ 13 ] However, no study directly comparing prevalences has been performed to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 14 , 15 ] Female gender has been associated with a higher prevalence of PRMDs among amateur musicians. [ 2 , 11 , 12 ] Playing load is another confirmed risk factor among amateur musicians. [ 8 , 9 , 11 ] A recent cohort study reported a nearly threefold increase in prevalence following a sudden increase in playing time.…”
Section: Introductionmentioning
confidence: 99%
“…These high physical loads predispose elite-level pianists to musculoskeletal disorders, as reflected by research which has shown piano to be associated with high rates of upper-extremity injuries in university-level performers [5]. Numerous terms have been used to describe musicians' musculoskeletal disorders, including 'overuse syndrome' [6][7][8], 'repetitive strain injury' [9,10] and 'cumulative trauma disorder' [11][12][13]. Lack of consensus regarding terminology has led to confusion in this field [14][15][16].…”
Section: Introductionmentioning
confidence: 99%